2004
DOI: 10.1021/ac030333p
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Characteristics of Neutral N-Linked Glycans Using a MALDI-TOF/TOF Tandem Mass Spectrometer

Abstract: The fragmentation characteristics of native and permethylated oligosaccharides using a matrix-assisted laser desorption/ionization (MALDI) time-of-flight/time-of-flight tandem mass spectrometer are described. The use of two MALDI matrixes, alpha-cyano-4-hydroxycinnamic acid (CHCA) and 2,5-dihydroxybenzoic acid (DHB), is shown to control the nature and extent of fragmentation observed in collision-induced dissociation experiments on synthetic oligosaccharides. CHCA promotes the occurrence of glycosidic cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 34 publications
6
96
0
Order By: Relevance
“…Following EDD of GAGs, hydrogen abstraction from Band C-type ions has also been noted, and observed as B Ϫ H, C Ϫ H, and C Ϫ 2H type ions [32,33]. Of particular interest is the product ion type C Ϫ 2H, which also has been reported by several investigators following positive-ion mode heCAD [58,[61][62][63][64] and which is observed following EDD of sialylated oligosaccharides in our examination. The complementary fragment for a C Ϫ 2H product ion would be a Z ϩ 2H species.…”
Section: Ms/ms Of Neutral Oligosaccharidessupporting
confidence: 80%
See 1 more Smart Citation
“…Following EDD of GAGs, hydrogen abstraction from Band C-type ions has also been noted, and observed as B Ϫ H, C Ϫ H, and C Ϫ 2H type ions [32,33]. Of particular interest is the product ion type C Ϫ 2H, which also has been reported by several investigators following positive-ion mode heCAD [58,[61][62][63][64] and which is observed following EDD of sialylated oligosaccharides in our examination. The complementary fragment for a C Ϫ 2H product ion would be a Z ϩ 2H species.…”
Section: Ms/ms Of Neutral Oligosaccharidessupporting
confidence: 80%
“…Another product ion is observed that is 2 Da lighter, and would appear to correspond to a loss of two hydrogens from this Y-type ion (or loss of one hydrogen from the radical Y-type species). Y Ϫ 2H product ions have also been observed following positive mode heCAD and are likely formed by a mechanism similar to C Ϫ 2H ions [62]. The product ion at m/z 833.27 has been assigned as a Y Ϫ 2H type product ion (Y 3␣ Ϫ 2H), but given that EDD of DSLNT resulted in significant internal cleavages, this ion could also be assigned C 4 /Y 4 Ϫ 2H.…”
Section: Ms/ms Of Sialylated Oligosaccharidesmentioning
confidence: 99%
“…Permethylated high mannose N-glycans have been studied by tandem mass spectrometry and their fragmentation patterns are well established [42,43]. RNase B contains exclusively high mannose oligosaccharides.…”
Section: Porous Graphite Lc/ms Of High Mannose N-glycans From Rnase Bmentioning
confidence: 99%
“…In addition, MALDI analyses suffer from matrix-dependent ionization and fragmentation processes [24 -27]. For instance, the "hot" matrix, ␣-cyano 4-hydroxycinnamic acid (CHCA), commonly used with peptides and small neutral glycans, is known to promote formation of glycosidic cleavages, whereas 2,5-dihydroxybenzoic acid (DHB), a "cooler" matrix that is typically used for glycopeptides and glycans, is said to suppress MALDI-induced fragmentation [24]. As a result, the type of matrix used for glycopeptide analysis largely influences the extent and type of fragmentation ions produced during MALDI-MS/MS experiments [26].…”
mentioning
confidence: 99%